Konstruksi Gender dalam Media Islam dan Sekuler: Analisis Framing Berita Poligami, Pernikahan Dini, dan KDRT - Umi Halwati; Imam Alfi; Johar Arifin; Retno Sirnopati (Jurnal Komunikasi Islam, 2022)
This article is a research report focusing on the construc–tion of Kompas and Republika's news coverage regarding gender-related issues such as polygamy, domestic violence, and early marriage. Zondhang Pan and Gerald M. Kosicki's framing analysis was applied to analyse six news articles published by Kompas and Republika in 2021. The findings illustrate that both Kompas and Republika tend to construct gender discourse to mainstream gender equality in order to "break the chain" of violence and oppression of women. In regard to polygamy, Republika as an Islamic-based me–dia has framed polygamy as a behaviour that is not recommended in Islam by highlighting very strict sharia requirements while cons–tructing the news coverage of polygamy. Kompas as the represent–tation of the secular media has framed polygamy as behaviour that leads to destruction rather than constructive behaviour for society.